Handbook of religious culture in nineteenth-century Europe - Steinhoff, Anthony J.; Zalar, Jeffrey T. (De Gruyter Oldenbourg reference, 2025)
This handbook offers a guide to research on religious culture during Europe's long nineteenth century (1800-1914). Grounded in the latest theoretical approaches and in line with trends that have produced a "religious turn" in the study of modern Europe, the volume assesses the state of the field while making provocative recommendations for its enlargement. Unique and ambitious in its thematic breadth, it addresses the histories of all five of Europe's main religious traditions - Eastern Orthodox Christianity, Judaism, Islam, Protestantism, and Roman Catholicism - and brings these histories into comparative analysis. This analysis extends to a wide range of subjects, from popular belief and practice, education and modern knowledge formation, and the arts to the intersections between religion and urbanization, civil society and politics, and missions and imperialism. It also evaluates recent developments in work on religion vis-à-vis both gender and nationalism, while calling attention to newer research that proposes secularism as a form of belief in its own right. Presenting the scholarship of eighteen leaders in their respective fields, the volume explains why religion as a topic of research has moved from the periphery to the center of modern European historiography